2018
DOI: 10.3390/act7020015
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinearities in Control Description and Design of an Electro Hydraulic Actuator for Flexible Nozzle Thrust Vector Control

Abstract: This paper presents all the significant nonlinearities that exist in the description of an electro hydraulic actuator for flexible nozzle thrust vector control. Starting from practical possibilities of the theory of a nonlinear system (which are based on the analyses of one nonlinearity or one equivalent nonlinearity in the proximity of the linear description of an actuator), this paper explores the possibilities of additional analyses of a nonlinear electro hydraulic actuator for flexible nozzle thrust vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Monte-Carlo results showed that the system with proposed control algorithm is robust and can respond with great performance characteristics despite of the wide range of disturbances that were considered. A comparison with another method presented in a previous work [24] revealed that the presented algorithm was successfully able to improve the steady state time, overshoot, and robustness in the presence of wide disturbance forces. These great performance characteristics make the proposed control algorithm suitable to aircraft applications which usually require accurate and fast responses.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Monte-Carlo results showed that the system with proposed control algorithm is robust and can respond with great performance characteristics despite of the wide range of disturbances that were considered. A comparison with another method presented in a previous work [24] revealed that the presented algorithm was successfully able to improve the steady state time, overshoot, and robustness in the presence of wide disturbance forces. These great performance characteristics make the proposed control algorithm suitable to aircraft applications which usually require accurate and fast responses.…”
Section: Discussionmentioning
confidence: 80%
“…The performance characteristics shown in these results confirm the effectiveness of the proposed control design. For instance, in a previous work [24] in which H-infinity controller was used, the actuator needed more than 2.5 seconds to reach the steady state condition with a maximum percentage overshoot of more than 20% when a disturbance force that was 78% of the maximum force generated by the actuator ( ) was applied while, for approximately the same amount of disturbance force, the current controller brings the system to the steady state desired value within about 0.1 second only and with zero percent overshoot.…”
Section: Stability and Performance Criteriamentioning
confidence: 98%
See 1 more Smart Citation